2021
DOI: 10.3389/fcvm.2021.726889
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Transplantation of Autologous Cardiac Micrografts During Coronary Artery Bypass Surgery

Abstract: Background: Cardio-regenerative cell therapies offer additional biologic support to coronary artery bypass surgery (CABG) and are aimed at functionally repairing the myocardium that suffers from or is damaged by ischemia. This non-randomized open-label study assessed the safety and feasibility of epicardial transplantation of atrial appendage micrografts (AAMs) in patients undergoing CABG surgery.Methods: Twelve consecutive patients destined for CABG surgery were included in the study. Six patients received AA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Based on our previous findings, we hypothesized that the LAA could serve as a regenerative tissue transplant after an MI [21][22][23][24][25][26][27]. The LAA is thin, exhibits a complex structure, and boasts many trabeculae, thus resembling ventricles more than the atria (Figure 1A,B and Supplementary Video S1).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Based on our previous findings, we hypothesized that the LAA could serve as a regenerative tissue transplant after an MI [21][22][23][24][25][26][27]. The LAA is thin, exhibits a complex structure, and boasts many trabeculae, thus resembling ventricles more than the atria (Figure 1A,B and Supplementary Video S1).…”
Section: Resultsmentioning
confidence: 91%
“…Our studies on the tissue composition of the murine LAA at the cellular level revealed cellular potential for cardiac regeneration in the LAA, putatively stemming from de novo cardiomyocyte formation and/or the paracrine effect by resident heart tissue macrophages [21,22]. Atrial-appendage-derived cells have been studied, by us and others, in animal models [23] and humans with promising results [24][25][26][27]. Atrial appendage tissue or micrograft transplants provide an autologous cardiac cell source and include all cardiac cell populations with their relevant extracellular matrix support.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Cells from the atrial appendages harbour paracrine potential and can induce cardiac regeneration (15)(16)(17)(18). In addition, the appendages can be readily harvested for cell therapies during coronary artery bypass grafting (CABG) (19,20). Recently, we reported the intraoperative grinding of right atrial appendage biopsy to micrografts (AAMs) and their epicardial transplantation safe and feasible during CABG in patients with ischemic HF with reduced ejection fraction (iHFrEF) and myocardial scar visible in cardiac magnetic resonance (CMR) with late gadolinium enhancement (n = 6, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported the intraoperative grinding of right atrial appendage biopsy to micrografts (AAMs) and their epicardial transplantation safe and feasible during CABG in patients with ischemic HF with reduced ejection fraction (iHFrEF) and myocardial scar visible in cardiac magnetic resonance (CMR) with late gadolinium enhancement (n = 6, Fig. 1) (19,20). Based on our clinical intraoperative processing of right atrial appendage (RAA) biopsy to AAMs and subsequent micrograft analysis, the method yielded > 90% cellular viability (n = 7) and a cell yield of 9.76 × 10 6 ± 0.53 / g of tissue (n = 11) (20).…”
Section: Introductionmentioning
confidence: 99%